Genotype by environment interaction in slash pine and methodologies comparison for radiata pine wood properties - Pagliarini, Maximiliano Kawahata [UNESP] (2016)
Exotic forest species have been introduced in Brazil in order to promote improvements in socioeconomic development and help to reduce the pressure caused to native forests. With growing demand for these species, research on genetic improvement has increased to find new, more productive germplasm and preferably in less time. Two species were used in the study: slash pine (Pinus elliottii Engelm. var. elliottii) and radiata pine (Pinus radiata D. Don). The first part of the study had the purpose to identify the stability, adaptability, productivity and genetic parameters, in addition to selection gain and genetic divergence in slash pine open pollinated second generation progenies considering phenotypic trait. Two tests were established, one in Ponta Grossa-PR with 24 progenies and one in Ribeirão Branco-SP with 44 progenies, both in Brazil, to identify the most productive genotypes for commercial planting areas in both sites. There was significant variation (p<0.01) among progenies for growth and form traits. The high coefficients of genetic variation for wood volume (14.31% to 16.24% - Ribeirão Branco-SP and 31.78% to 33.77% - Ponta Grossa-PR) and heritability (0.10 to 0.15 – Ribeirão Branco-SP and 0.36 to 0.48 – Ponta Grossa-PR) have shown low environmental influence on phenotypic variation, which is important for the prediction of genetic gain by selecting and confirming genetic potential in both places, especially Ponta Grossa. The effect of genotype x environment interaction is simple. Progenies planted in one site can also be planted in the other. Among these C-197, C-189-1, C-084-2 and C-032-2 progenies are suitable for plantations in both studied region of São Paulo and Paraná. Although larger number of progenies in Ribeirão Branco, it was found the same number of clusters through UPGMA and Tocher methods in both tests. There is genetic diversity among slash pine progenies. For breeding programs, it is recommended to cross progenies between different groups to increase genetic variation, and consequently the genetic gain in subsequent generations, not forgetting to take into account the performance of interest trait. The objective of the study in Radiata pine was relate wood quality traits obtained from two methods Pilodyn and SilviScan to validate an efficient phenotyping methodology for a greater number of samples. A test with 30 progenies of Radiata pine was established in Flynn Australia. The evaluated traits were wood density, microfibril ange and modulus of elasticity. Genetic and phenotypic correlation between traits of wood quality obtained from two methods and narrow-sense individual heritability were estimated. The Pilodyn data showed high heritability and high genetic and phenotypic correlation between wood density and moderate with microfibril angle and modulus of elasticity. The results confirm that the Pylodyn is an effective indirect and rapid method for evaluation of genetic parameters for wood quality traits in Radiata pine.